ChemInform Abstract: Three‐Component Reaction for Construction of Spiro[indoline‐3, 7′‐thiazolo[3, 2‐a]pyridines] and Spiro[benzo[4, 5]thiazolo[3, 2‐a]pyridine‐3, 3′‐indolines]. Issue 18 (April 2016) - Yang, Fan; Sun, Jing; Yan, Chaoguo
Abstract: The title compounds are obtained as mixture of cis/trans‐isomers.